2012
DOI: 10.1021/es302313h
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Tc Dynamics in a Bioreduced Sediment: An Investigation with Gamma Camera Imaging of 99mTc-Pertechnetate and 99mTc-DTPA

Abstract: We demonstrate the utility of nuclear medical imaging technologies and a readily available radiotracer, [(99m)Tc]TcO(4)(-), for the noninvasive monitoring of Fe(II) production in acetate-stimulated sediments from Old Rifle, CO, USA. Microcosms consisting of sediment in artificial groundwater media amended with acetate were probed by repeated injection of radiotracer over three weeks. Gamma camera imaging was used to noninvasively quantify the rate and extent of [(99m)Tc]TcO(4)(-) partitioning from solution to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…The medical radiotracer 99m Tc (half-life 6 h), allows high resolution imaging of sediments containing ultra-trace concentrations of 99m Tc (typically < 5 £ 10 ¡10 mol l ¡1 ) making it possible to conduct studies at technetium concentrations typical of far field contamination at nuclear sites down gradient of the contaminant plume source Corkhill et al 2013;Lear et al 2010;Vandehey et al 2012), and below the theoretical solubility limit of hydrous TcO 2 (»10 ¡8 mol l ¡1 ; Hess et al 2004). At these environmentally relevant concentrations of contaminant, bioavailable Fe will be in stoichiometric excess in typical bioreduced sediments and the rate of Tc(VII) reduction, and the mobility of 99 Tc will be controlled by the Fe(II) speciation Peretyazhko et al 2012;Wildung et al 2004).…”
Section: Mmentioning
confidence: 99%
See 1 more Smart Citation
“…The medical radiotracer 99m Tc (half-life 6 h), allows high resolution imaging of sediments containing ultra-trace concentrations of 99m Tc (typically < 5 £ 10 ¡10 mol l ¡1 ) making it possible to conduct studies at technetium concentrations typical of far field contamination at nuclear sites down gradient of the contaminant plume source Corkhill et al 2013;Lear et al 2010;Vandehey et al 2012), and below the theoretical solubility limit of hydrous TcO 2 (»10 ¡8 mol l ¡1 ; Hess et al 2004). At these environmentally relevant concentrations of contaminant, bioavailable Fe will be in stoichiometric excess in typical bioreduced sediments and the rate of Tc(VII) reduction, and the mobility of 99 Tc will be controlled by the Fe(II) speciation Peretyazhko et al 2012;Wildung et al 2004).…”
Section: Mmentioning
confidence: 99%
“…Imaging experiments using 99m Tc(VII) have been conducted in sediment microcosms under variable geochemical conditions demonstrating that 99m Tc is retained on Fe(III)-reducing sediments at ultra-trace concentrations and proposing reduction to Tc(IV) and sorption to biomineral surfaces as the retention mechanism Lear et al 2010;Vandehey et al 2012). Under flow conditions in oxic column, experiments focussed on radioactive waste disposal demonstrated that 99m Tc(VII) sorption was weak and that under oxic conditions 99m Tc acted as a conservative tracer (Corkhill et al 2013).…”
Section: Mmentioning
confidence: 99%
“…The exact nature of this effect is unclear, although it is unlikely that it is caused by chemical absorption of 99m Tc-DTPA, which is shown to be a conservative tracer for Rifle sediments in (Vandehey et al, 2011). …”
Section: Resultsmentioning
confidence: 99%
“…During the 30-minute interval of activity delivery, the HPLC pump rate was reduced to 1.15 mL/min, thus achieving a constant flow rate at the inlet of 1.25 mL/min and a 30 minute-wide rectangle-shaped radiotracer input function. The testing and characterization of the 99m Tc-DTPA as a conservative tracer is described elsewhere (Vandehey et al, 2011). …”
Section: Methodsmentioning
confidence: 99%
“…For example, single photon emission computed tomography (SPECT) has been used to dynamically measure the 2D and 3D distribution of 99m TcO 4 and 99m Tc-DTPA in porous media (Boutchko et al, 2012;Lear et al, 2010), while positron emission tomography (PET) has been used similarly with F - (Kinsella et al, 2012). In a natural sediment subjected to iron and sulfate reduction, Vandehey et al (2012) found that 99m Tc-DTPA remained soluble while 99m TcO 4 precipitated. While these early trials demonstrate the utility of radiotracer compounds under some conditions, knowing more about the reactivity of these compounds would enable better selection of radiotracer compounds for a given system.…”
mentioning
confidence: 99%